PUTUSAN MAHKAMAH KONSTITUSI NOMOR 140/PUU-VII/2009 DAN JAMINAN KONSTITUSIONAL ISLAM NUSANTARA - Eddyono, Luthfi Widagdo (Analisis: Jurnal Studi Keislaman, 2015)
The Constitutional Court  Decision  Number  140/PUU-VII/2009 regarding  the case of judicial  review of Law No. 1/PNPS/1965 about   the   Prevention   of  Abuse   and/or   blasphemy   is   very important  for the study  of the development  of religious  life in Indonesia,  especially  for the  study  of “Islam  Nusantara”.  This paper will describe ebates  in the trial  to assessed the extent  to which the views of the majority  of the people related  with  the norms of the Law. In addition, this paper also will be describe the Constitutional Court’s  decision  on the  petition.  After  that,  the authors examine the relationship between the Constitutional Court decision and the existence of “Islam Nusantara”  in Indonesia. In conclusion, the Constitutional Court through Decision No. 140/ PUU-VII/2009  provided constitutional guarantees  on  religious practices like “Islam Nusantara”.